Impact of Chhath festival on health seeking behaviour of local population - Pandey, Avinash; Singh, Anjana; Singh, Shivkant; Kumar, Amit; Shahi, Heena; Kumari, Aishwarya (International Journal Of Community Medicine And Public Health, 2019)
Background: There is lack of information regarding health seeking behaviour of local population during Chhath puja. The aim is to evaluate health seeking behaviour of local population during Chhath festival. And the main objectives is to evaluate the extent of change of routine visits of people seeking healthcare during Chhath festival across major super speciality departments of government hospital. Methods: Database of outpatient department visits across nine super specialities namely, cardiology, gastroenterology, gastrointestinal surgery, neurology, neurosurgery, nephrology, urology, paediatric surgery and oncology were obtained for year 2016, 2017 and 2018 from hospital records. Median and maximum number of outpatient visits per month of each of the nine specialities per year was compared with number of outpatient visits during Chhath festival month of corresponding year. Results: In year 2018, there was 18% average absolute decline of outpatient visit during Chhath month compared to median number of outpatient visits per month that year. Similarly, the average absolute decline of OPD visits was 32% during Chhath month compared to the month when there was maximum number of outpatient visits in 2018. Cardiology, gastroenterology, neurology, nephrology and oncology had more than 20% absolute decline in 2018 compared to median. Trends was similar in year 2017 and 2016, with average decline in Chhath month compared to median and maximum outpatient visits in corresponding year as 3%, 14%, 10% and 26% respectively. Conclusions: Health seeking behaviour of local population drops by one fifth during Chhath festival. Fall in outpatient visits is consistent, uniform and recurring every year.